The Role of Local and Remote Processes for Wintertime Surface Energy Budget Extremes over Arctic Sea Ice - Papritz, Lukas; id_orcid:0 000-0002-2047-9544; Murto, Sonja; Röthlisberger, Matthias; id_orcid:0 000-0003-0904-9495; Caballero, Rodrigo; Messori, Gabriele; Svensson, Gunilla; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of Climate, 2023)
ISSN:0894-8755 ISSN:1520-0442